Key initiatives to successfully manage collaborative university-industry R&D: IC-HMI case study - Fernandes, Aldora Gabriela Gomes (2019)
This paper describes the results of a qualitative study to identify the key management initiatives in a successful university-industry (UI) collaborative funded program between the University of Minho (UMinho) and Bosch Car Multimedia Portugal (Bosch), named IC-HMI. The IC-HMI program embraced an overall investment of 54.7 M€ and involved around 500 people throughout the Program's duration (2015-2018). While the literature provides some advice on managing programs and projects, the specific context of UI R&D collaboration is being scarcely reported, demanding a strong research effort to produce effective guidelines. The IC-HMI is considered a successful program for several reasons, as evidenced by the decision of UMinho and Bosch partners to develop a subsequent R&D collaborative program from 2018 to 2021, doubling its investment. The success attained with the IC-HMI program could be somehow explained by key management initiatives adopted, such as the: creation of Program and Project Management Office, definition and communication of a Governance Model, creation of Project Charters, promotion of Alignment Stakeholders Workshops, Project Progress Meetings and creation of Project Transition Plans, among other key initiatives reported in this paper.